2000
DOI: 10.1093/jn/130.6.1548
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid Reduces Rat Adipose Tissue Cell Size Rather than Cell Number

Abstract: We investigated the basis for the reduction in fat pad size in rats fed conjugated linoleic acid (CLA). In the first study, growing female Sprague-Dawley rats (initial weight150 g) were fed diets containing 0, 0.25 and 0.5 g/100 g diet of a purified (97% CLA) and 0.5% of a feed-grade (55% CLA) source of CLA for 5 wk to determine the effects on growth performance and fat mass. There was no effect of CLA on growth rate or food intake. Dietary CLA reduced retroperitoneal fat pad weight 13, 25 and 32% in rats fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
130
3
18

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(175 citation statements)
references
References 26 publications
24
130
3
18
Order By: Relevance
“…Kang et al [3] found an increase in FAS mRNA induced by 0.2% trans-10,cis-12 CLA feeding for 4 weeks in mice. In contrast, Azain et al [4] did not find changes in FAS activity induced by CLA feeding in rats. Other authors found reduced expression of FAS and ACC in mice [5,6] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Kang et al [3] found an increase in FAS mRNA induced by 0.2% trans-10,cis-12 CLA feeding for 4 weeks in mice. In contrast, Azain et al [4] did not find changes in FAS activity induced by CLA feeding in rats. Other authors found reduced expression of FAS and ACC in mice [5,6] .…”
Section: Discussionmentioning
confidence: 80%
“…In some of these trials, hepatic triacylglycerol content was measured and it was concluded that hepatomegaly was due to lipid accumulation [5,[14][15][16]. In contrast, the studies performed on rats reported no effects on liver weight induced by CLA [4,10,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…A partir de então muitos foram os estudos com diversos animais [102][103][104] , com culturas de adipócito de roedores e humanos [105][106][107][108][109] e com humanos 8,65,[74][75][76][77][78][79][80]90,95,96,[110][111][112][113][114][115][116] , que surgiram com o objetivo de avaliar a propriedade de redução da gordura corporal, bem como elucidar os mecanismos de ação pelos quais o CLA desempenha esse papel.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified
“…Na verdade, os estudos apontam que a redução da gordura corporal induzida pelo CLA ocorre não somente pela diminuição do número de adipócitos, mas também, ou até mesmo somente, pela redução do seu tamanho. Considerando que o tamanho da célula adiposa está diretamente relacionado com o conteúdo de triacilgliceróis em seu interior, a redução desse lípide induzida pelo CLA resultaria, conseqüentemente, na diminuição do tamanho da célula 3,102,108 . É importante discutir que o mecanismo de ação responsável pela redução de triacilgliceróis induzida pelo CLA ainda necessita de maiores esclarecimentos.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified
“…Mixtures of conjugated linoleic acid isomers (CLA) were initially shown to reduce the percentage of whole body fat and/or the mass of fat pads, in mice [1] and then in rats, hamsters, pigs and hu-CLA feeding had no effect on these parameters in mice [4], rats [5][6][7][8][9][10], hamsters [9,11] and humans [12]. In other studies, CLA increased body protein concentration or lean body percentage without modification of absolute amounts, in mice [13][14][15], rats [16] and humans [17,18].…”
Section: Introductionmentioning
confidence: 99%